FRI0359 Routine clinical pathology measurements are associated with risk of organ damage accrual in sle. (12th June 2018) - Zhang, K.; Boyd, S.; Petitjean, F.; Hoi, A.; Koelmeyer, R.; Morand, E.; Nim, H.
Abstract : Background: Prevention of permanent organ damage, a major predictor of morbidity and mortality, is a key goal in the treatment of SLE. Physician-measured disease activity scores, which entail some subjectivity, are associated with damage accrual risk, but there have been few studies of objective measures as indicators of organ damage risk. Routine pathology laboratory measurements provide objective biological data, but their association with damage accrual in SLE has not been studied. Objectives: To evaluate the association of objective pathology laboratory measurements with risk of organ damage accrual in SLE. Methods: A dataset of SLE patients between 2007–2017 from the Australian Lupus Registry and Biobank was studied. Variables recorded prospectively included disease activity (SLEDAI-2k), drug treatment and 16 routine pathology measurements at each visit, and organ damage (SLICC-SDI) annually. Longitudinal patient data was split into annual periods, and each visit classified as being either in a "transition" or "non-transition" period based on whether SDI increased during that period. Time adjusted means (TAMs) of the variables were calculated for each period, and multivariable logistic regression analysis of the association with being in a "transition" period (adjusting for age, gender, race, previous organ damage and prednisolone dose) was performed, with Holm-Bonferroni correction. An "odds ratio plot" was generated to depict the effect on risk of organ damage accrual at each threshold of the continuous variables. Results: 893 periods, comprising 5082 visits from 245 patients (85.6% female, 50.2% Caucasian), were analysed. Five out of 16 laboratory variables: estimated glomerular filtration rate (eGFR), creatinine (p<0.01), urine protein:creatinine ratio (p<0.01), ESR (p<0.001), and haemoglobin (p<0.001) were significantly associated with risk of damage increase. Moreover, the odds of damage increase were approximately proportional to the deviation of each of these variables from its respective normal range. SLEDAI-2k was also significantly associated with damage increase (p<0.001), but the association of SLEDAI-2k with damage did not exhibit this proportionality. Conclusions: Routine pathology measures were found to be proportionally associated with organ damage risk in SLE. The potential for the use of these measures as biomarkers, for example to generate an organ damage risk calculator for SLE, warrants further research. Disclosure of Interest: None declared